2017
DOI: 10.1055/s-0037-1603793
|View full text |Cite
|
Sign up to set email alerts
|

Early Outpatient Physical Therapy May Improve Range-of-Motion in Primary Total Knee Arthroplasty

Abstract: Knee stiffness is a relatively common complication following a primary total knee arthroplasty (TKA). Following this procedure, rehabilitation is essential to maintain, improve, and prevent the loss of knee range-of-motion (ROM). Currently, there is a paucity of studies describing whether the timing of physical therapy (PT) post-TKA plays a role in ROM outcomes. Therefore, the purpose of this study was to compare (1) flexion and (2) extension ROM at final follow-up of TKA patients who either began outpatient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The improvement in knee flexion was better in the logbook group than that in the non-logbook group at 24-week post-operatively, although the differrence was not statistically significant (p = 0.263). Similarly, McGinn et al studied early outpatient physical therapy within six weeks and found that early post-operative physical therapy resulted in greater knee flexion and extension than late physical therapy (13) .…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in knee flexion was better in the logbook group than that in the non-logbook group at 24-week post-operatively, although the differrence was not statistically significant (p = 0.263). Similarly, McGinn et al studied early outpatient physical therapy within six weeks and found that early post-operative physical therapy resulted in greater knee flexion and extension than late physical therapy (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging early follow-up or additional interventions with in-home or early transition to outpatient physical therapy could be beneficial to this population. 11 Bong and Di Cesare reviewed previous studies that measured the effectiveness of manipulations post TKA. 10 They recognized the importance of early mobilization through physical therapy post TKA, and found that MUAs are most successful within the 3-month postoperative window if aggressive physical therapy results in little to no gains in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…McGinn et al found that patients who attended outpatient physical therapy within the first 6 weeks post TKA had better mean flexion than those who waited more than six weeks to begin their physical therapy program. 11 In light of recent interest in cost-saving measures related to TKA, ROM at discharge may be an important indicator for patients that will incur greater cost without greater physician attentiveness and education. With knowledge of this association between discharge ROM and MUA, patients may be better risk stratified very early in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The timeline of a postoperative rehabilitation course after a total knee replacement is as follows: (I) acute inpatient PT lasts 1 to 3 days; (II) outpatient PT lasting 1 to 6 weeks focusing on passive range of motion (ROM), normal ambulation, and improving quadriceps strength; (III) returning to normal, everyday activity in 4 to 8 weeks (14). The modalities used for each patient were previously published as the multimodal approach (15). Discharge from PT occurs when the therapist determines the patient has reached maximum medical improvement, where there is no longer a benefit of continued PT, or has returned to an everyday functional level of activity.…”
Section: Outpatient Pt Protocolmentioning
confidence: 99%